IMPLEMENTATION OF REGIONAL DEVELOPMENT CONCEPT BASED ON AIRPORT IN WEST JAVA INTERNATIONAL AIRPORT AND SURROUNDING AREAS - Din Haq, Harun
West Java International Airport is located in Kertajati Subdistrict, one of the sub-districts in the north of Majalengka Regency, which was inaugurated in mid- 2018 and has been operating for about one year until now. However, it is feared that the current plans and conditions of the existing spatial plan are not yet under the concept of airport-based area development and the impact of the surrounding area is currently unknown. The purpose of this study is to determine the suitability of existing plan documents and conditions with the concept of airport-based area development and to know stakeholder perspectives related to the concept of airportbased area development that should developed first and the impact of BIJB on the surrounding area at this time as recommendations for the development of the West Java International Airport and the surrounding areas. Qualitative descriptive method is used to justify the assessment of the plan through the government's plan documents and the existing condition of the spatial plan of BIJB and surrounding areas through field observations with the concept of airport-based area development and to find out the impact caused by BIJB on the surrounding area through interviews of 14 village officials in Kertajati subdistrict. The next method uses importance-performance analysis by collecting data through interviews with the government and reviewing user responses from 5 social media owned by PT.BIJB to determine stakeholder perceptions about what variables should be prioritized for the progress of BIJB and the surrounding areas. The results are distance, zoning, design and 15 other variables out of 37 variables, which have planned documents and existing conditions under the concept. Then there are integration, land use, business areas, and 7 other variables which according to the government are the first priority and distance, the potential increase in passengers and cargo, and the airport as a catalyst and magnet in business development which according to users is the first priority. The impact of BIJB on the surrounding area has not yet given maximum positive social and economic impacts, has many negative social impacts but has not yet had a negative impact on the environment. The recommendations of this study are the improvement of variables that are not under the concept of airport-based area development by the government. Coordination needs to be done to realize the first priority variable according to the government and users in this study and then increase the positive impacts and reduce the negative impacts of BIJB on the surrounding areas identified in this study.